Methods for modeling overdispersed outcomes with application to disease incidence rates macrobenthic fauna densities - Noodchanath, Kongchouy (Prince of Songkla University, 2012)
Thesis (Ph.D.(Research Methodology))--Prince of Songkla University, 2010